Improvement of gut microbiome and intestinal permeability following splenectomy plus pericardial devascularization in hepatitis B virus-related cirrhotic portal hypertension - Zhao, Yang; Zhou, Rui; Guo, Ying; Chen, Xi; Zhang, Aiyu; Wang, Jiayin; Ji, Fanpu; Qin, Bowen; Geng, Jing; Kong, Guangyao; Li, Zongfang (Frontiers in Immunology, 2022)
The gut microbiome is an essential component of the intestinal mucosal barrier, critical in regulating intestinal permeability. Microbiome dysbiosis and intestinal permeability changes are commonly encountered conditions in patients with cirrhosis and are closely related to its development and further complications. However, alterations in the gut microbiome and intestinal permeability in chronic hepatitis B virus (HBV) patients with cirrhotic portal hypertension after undergoing a splenectomy plus pericardial devascularization (SPD) have not been investigated. This study recruited 22 patients who were measured against themselves on the study parameters before and after an SPD, along with 20 healthy controls. Methodologically, fecal samples were collected for gut microbiome analysis by 16S ribosomal DNA sequencing, and peripheral blood samples were obtained to examine the liver and intestinal permeability. This study showed that the community structure of the gut microbiomes in patients before the SPD exhibited obvious differences from those in the healthy control group. They also exhibited a decreased bacterial community richness, increased intestinal permeability, and enhanced inflammation compared with the healthy controls. These issues were further aggravated two weeks after the SPD. There was also evidence of significantly higher abundances of Streptococcaceae, Enterobacteriaceae, and Enterococcaceae than those in the healthy control group. However, 12 months after the surgery, 12 of the 16 patient-associated genera recovered, of which 10 reached normal levels. Additionally, the microbiome diversity increased; the bacterial composition was back to a level similar to the healthy controls. Liver function, intestinal permeability, and inflammation levels all improved compared with preoperative levels. Furthermore, correlation analyses indicated that the five recovered bacterial taxa and the Shannon diversity index were correlated with several improved clinical indicators. Altogether, the improvements in the liver and intestinal permeability in HBV-related cirrhotic patients may be related to the restoration of the gut microbiome after an SPD.